Effects of short high impact plyometric training on jumping performance in female volleyball players - Kristicevic, T.; Krakan, I.; Baic, M. (Acta Kinesiologica, 2016)
Fifty four female volleyball players participated in this study (15±1). The aim of this research is to determine the effects of 5 week plyometric training in female volleyball players. Standard anthropometry (height, standing-reach height, body mass, vertical jumps and specific volleyball jumps were the tests selected. The experimental and control groups were well matched on the pre-training tests with no significant differences found for any variable between the two groups. A five-week-long training program was applied in plyometric group. There was significant interaction between the groups for Squat jump. Plyometric training induced significant improvements in SJ and CMJ. However, control group showed no significant improvements in any vertical jump test. In conclusion, the completion of a 5 week plyometric training program improved selected vertical jump tests in young female volleyball players. However, there were no significant changes in spike and block jumps following the plyometric training program.